Cross-border mobility of migrant households under COVID-19 in Argentina - Diaz, Mariela Paula (Revista de Estudios Andaluces, 2023)
The main objective is to analyze the links between Bolivian migrant households residing in Villa 20 of the City of Buenos Aires (Argentina) with their country of origin. Specifically, to investigate the characteristics of multi-local practices and the impact of border closures in the global context of the COVID-19 pandemic. To carry out this work, a multi-method methodological strategy was used that combines qualitative and quantitative procedures. Among the main results, the practice of plurilocality stands out as part of family reproduction strategies on a scale that exceeds the limits of the neighborhood. The government measure to close borders in the face of the pandemic generated a decrease in this type of cross-border mobility, but informally increased others.